Tracheal Intubation in Emergency Departments in China: A National Cross-Sectional Survey - Dai, Yili; Walline, Joseph Harold; Yu, Heng; Zhu, Huadong; Xu, Jun; Yu, Xuezhong (Frontiers in Medicine, 2022)
Background: Tracheal intubation is a necessary but risky procedure often performed in emergency departments (EDs) around the world. Relatively high morbidity has been encountered in Chinese EDs, which has raised concern on peri-intubation ED management. This study aimed to investigate intubation procedures and identify any areas for improvement in Chinese EDs. Methods: This was a questionnaire-based survey lasting one month (March, 2021) in 41 tertiary-care hospital EDs in China. The survey queried general characteristics of ED patients and intubation situations. The primary outcome was complications associated with the intubation. The secondary outcomes were the first successful pass rate and blood pressure variation during the intubation. Univariate and binary logistic regression analyses were used to find possible risk factors of complications and the first-pass intubation success. Results: 1020 replies were analyzed out of 1080 surveys submitted (94.4% response). Most patients were elderly males with severe conditions like cardiac arrest (24.8%). 97.2% of patients were given preoxygenation, and 48.1% received some form of pretreatment. Induction drugs (e.g. etomidate, ketamine) were less often used, 39.8% of intubations used sedatives, 5.5% used analgesics, and only 5.3% used muscle relaxants. The overall first-pass intubation success rate was 85.7% and was accompanied by a 19.8% adverse event rate. A marked decrease in blood pressure after intubation was also identified. Conclusions: This survey found a tracheal intubation first-pass success rate of 85.7% and a 19.8% adverse event rate. Given the very low use of induction medications (5.3% use of muscle relaxants), future education should focus on induction drugs as well as traditional intubation techniques.